Plasticized lithium iodide‑doped polyacrylonitrile‑methylcellulose blend electrolytes for supercapacitor application - Shamsuri, N. A.; Rojudi, Z. E.; Vicxeant, V. T.; Noor, I. M.; Kadir, M. F. Z.; Shukur, M. F. (Springer Science and Business Media, 2023)
This paper reports the characterisation and application of plasticized polyacrylonitrile (PAN)-methylcellulose (MC) doped with lithium iodide (LiI) in a symmetric supercapacitor at ambient temperature. From Fourier transform infrared spectroscopy (FTIR) analysis, the shifting of hydroxyl (OH) band to a lower wavenumber upon addition of glycerol to the PAN-MC-LiI evidences the interaction between the materials at OH groups. X-ray diffraction (XRD) analysis reveals that the electrolyte with 20 wt. glycerol (PMG20) has the lowest degree of crystallinity. This XRD result reflects the increase in conductivity as PMG20 obtains the highest room temperature conductivity of (1.54 ± 0.40) × 10–3 S cm−1. Field emission scanning electron microscopy (FESEM) analysis shows that there are changes in surface morphology as LiI and glycerol are added to PAN/MC. The tion of PMG20 is 0.93 indicating that the ions are the dominant charge carriers. From linear sweep voltammetry (LSV), PMG20 is electrochemically stable up to 2.1 V. An electrochemical double layer capacitor (EDLC), which is a type of supercapacitor, is fabricated by sandwiching PMG20 between a pair of activated carbon-based electrodes and is characterised using cyclic voltammetry (CV) and galvanostatic charge–discharge (GCD) analysis. The highest specific capacitance of single electrode (Csp) obtained from CV is 16 F g−1. The EDLC is charged and discharged for 100 cycles at 1.0 mA cm−2 with Csp between 28.08 and 15.76 F g−1.